2017
DOI: 10.1111/ene.13398
|View full text |Cite
|
Sign up to set email alerts
|

More than constipation – bowel symptoms in Parkinson's disease and their connection to gut microbiota

Abstract: Our results indicate that PD patients may suffer from colonic dysfunction beyond pure constipation. Therefore, a more comprehensive assessment of bowel symptoms could provide valuable information. The lower abundance of Prevotella bacteria in PD patients with IBS-like symptoms suggests that the microbiota-gut-brain axis may be implicated in the gastrointestinal dysfunction of PD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
117
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 122 publications
(125 citation statements)
references
References 28 publications
6
117
1
1
Order By: Relevance
“…Several other genera and OTUs including Anaerotruncus and Clostridium XIVb showed associations with motor and nonmotor symptoms . This supports previous reports of connections between motor and nonmotor symptoms and gut microbiota …”
supporting
confidence: 91%
See 2 more Smart Citations
“…Several other genera and OTUs including Anaerotruncus and Clostridium XIVb showed associations with motor and nonmotor symptoms . This supports previous reports of connections between motor and nonmotor symptoms and gut microbiota …”
supporting
confidence: 91%
“…As in this study, a significant proportion of RBD patients also reported constipation, the same limitation also applies to the RBD‐related findings. Gut microbiome composition, in particular abundance of Akkermansia and Prevotella , clearly correlates with gastrointestinal symptoms, transit time and stool consistency . Therefore, it is not clear whether these changes are merely a consequence of PD‐related gut dysfunction or whether they are a contributing factor.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…16 In PD, several studies have described alterations of gut microbiota composition, and changes in fecal microbiota abundance have been found to be associated with gastrointestinal and motor symptoms. 17,18 However, the cause of these changes is not known. We hypothesized that higher antibiotic exposure is associated with increased PD risk.…”
mentioning
confidence: 99%
“…In addition, disturbances of gut function such as constipation have been described in patients [reviewed in 29]. Using the Rome III questionnaire, Mertsalmi et al [40] investigated the incidence of inflammatory bowel syndrome-like symptoms in 74 PD patients and 75 healthy controls. These symptoms were found to be elevated in 24.3% of the PD patients versus 5.3% of controls.…”
Section: Impact Of Gut Microbiota On Neurodegenerative Diseasesmentioning
confidence: 99%